Sporogenesis, gametogenesis and pollen morphology of Solanum japonense and S. septemlobum (Solanaceae) - Liu, Yanshuang; Gu, Lei; Liu, Jiaxi (Archives of Biological Sciences, 2018)
Solanum japonense Nakai and S. septemlobum Bunge are medicinal plants used chaotically in traditional Chinese medicine because they have the same Chinese name, Shuyangquan. In this study, anther wall development, microsporogenesis, male gametophyte development, megasporogenesis and female gametophyte development of S. japonense and S. septemlobum were studied using traditional paraffin section technology for the first time, and their pollen morphologies were compared using scanning electron microscopy. The results showed that both species exhibit dicotyledonous anther wall development, dual tapetum origination, secretory tapetum development, simultaneous microsporocyte cytokinesis, tetrahedral tetrad, coexistent 2-celled and 3-celled mature spheroidal pollen grains that are circular along the equatorial view and have tricolporate groves, 2 locules per ovary, axial placenta, anatropous, unitegmic and tenuinucellate ovule, linear megaspore tetrad, as well as monosporic Polygonum type of embryo sac, where the chalazal megaspore develops into the functional megaspore and the other three megaspores degenerate. However, the pollen grains of S. japonense are circular along the polar view, while those of S. septemlobum are triangular; the pollen surface ornamentation of S. japonense is granulate-verrucate-punctate, while that of S. septemlobum is granulate-punctate-fossula. These results enrich the embryological data of Solanum and provide palynological bases for the classification of these two species. https://doi.org/10.2298/ABS170724048L Received: July 24, 2017; Revised: October 20, 2017; Accepted: November 9, 2017; Published online: November 22, 2017 How to cite this article: Liu Y, Gu L, Liu J. Sporogenesis, gametogenesis and pollen morphology of Solanum japonense and S. septemlobum (Solanaceae). Arch Biol Sci. 2018;70(2):313-20.